Association of physical activity and screen time with vitamin D status among children with disabilities - Wang, Wen; Wang, Zhe; Sun, Haixia; Li, Guowei; Liu, Su; Xue, Zheng (Frontiers in Pediatrics, 2025)
BackgroundPhysical activity (PA) and screen time (ST) may influence vitamin D status in children with disabilities, yet their relationships remain understudied in this population.MethodsWe analyzed data from 645 children with disabilities aged 3–19 years. PA and ST were categorized into quartiles. Multiple linear regression models were used to examine associations between PA, ST, and vitamin D levels, adjusting for demographic and clinical characteristics.ResultsHigher PA was positively associated with vitamin D levels (β = 0.984, 95% CI: 0.388–1.58, p = 0.003) in fully adjusted models. Participants in the highest PA quartile had significantly higher vitamin D levels compared to the lowest quartile (β = 6.884, 95% CI: 2.736–11.031, p = 0.003). Conversely, ST showed an inverse association with vitamin D levels (β = −0.8, 95% CI: −1.414 to −0.186, p = 0.015), with the highest ST quartile showing significantly lower vitamin D levels compared to the lowest quartile (β = −8.098, 95% CI: −13.318 to −2.877, p = 0.005). Males were more likely to engage in high PA (66.31%), and both PA and ST showed significant age-related patterns.ConclusionsOur findings reveal clear links between physical activity, screen time, and vitamin D levels in children with disabilities. Promoting physical activity and reducing screen time may be effective strategies to improve vitamin D status in this population.